Application of a time-delayed control system in vibration suppression - Jie Liu; Kefu Liu; Hao Bai (IEEE International Conference Mechatronics and Automation, 2005, 2005)
This paper provides a new perspective on the design of a time-delayed active vibration absorber, which can eliminate the vibration of the primary structure subject to a sinusoidal disturbance. This control system features one output feedback. The close relationship between the time-delayed active vibration absorber and the traditional PD controller is revisited with an assistance of a vector interpretation. The stability of the combined system is discussed. The attention is focused on the difficulty of maintaining the stability of the combined system while achieving a marginal stability of the absorber system. An electromagnetic active vibration absorber is developed. An online tuning strategy is developed to automatically find the optimum gain while the delay time is fixed. The experimental results show that the proposed control system can suppress the vibration of the primary system significantly.